STATUS TROFIK DAN DAYA TAMPUNG BEBAN PENCEMARAN AIR LIMBAH BUDIDAYA IKAN KJA DI WADUK KOTO PANJANG - Hari Haryanto; Thamrin ' Thamrin; Sukendi ' Sukendi (Jurnal Ilmu Lingkungan, 2014)
The aims of this research are to identify water quality concerning to chemical-physicaland biological aspects and the present trophic condition of Koto Panjang Reservoir andits pollution load carrying capacity to support freshwater floating net cageaquacultureand total phosphate concentration to determine load carrying capacity.These ranges of values showed that this area is classifed as an eutroph to hypereutrophwaters. Pollution load carrying capacity of the Koto Panjang reservoir when the annualproductivity is estimated as high as 2.186 ton/year. The conclusion of this research isoptimum number of floating net cage that can operated in research location are 182unit.